RACISM AND MATHEMATICS EDUCATION WHAT ARE THE EFFECTS OF RACISM THAT CONTINUE TO LINGER IN MATHEMATICS CLASSROOMS? - Adetoro Ince, Jamaal [UNESP] (Universidade Federal de Sao Paulo, 2024)
This paper seeks to discuss the connections between racism and the mathematics education Black students receive in the urban mathematics classroom in the city of Newark. Racism continues to exist in this world and has been reformed in systematic ways in our society, and with these reforms there exists inequality in quality mathematics education offered to Black students, and as a result less future opportunities in mathematics related fields. This article will highlight experiences of the author and analyzed data from the students of Newark. To connect these experiences with current racist systems first a brief history of the origins of racism is discussed as well as the implications of racial identities and how that can affect certain groups of people. Then a conceptual framework is explained which was used to analyze the experiences which include the concepts of: racial identity, mathematical identity, and foregrounds. Then there are different topics of racism in education discussed such as the apparent disconnection between racism and mathematics education although there disparities and inequalities in the mathematics opportunities offered and the way that Black people are portrayed in society in general. The paper ends with a review of the data analysis to learn about the perspectives of students and their thoughts on race and the mathematics education that they receive.
RACISMO Y EDUCACIÓN MATEMÁTICA ¿Cuáles son los efectos del racismo que persisten en las aulas de matemáticas?
RACISMO E EDUCAÇÃO MATEMÁTICA Quais são os efeitos do racismo que continuam a persistir nas salas de aula de matemática?
Keywords: black students; foregrounds; mathematical identities; racism